Investigating the distribution of colloidal and nanoparticulate gold particles in Archean orogenic gold systems on the Kaapvaal and Zimbabwe Cratons - Mangwaya, Langton Tapiwanashe (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.